Efficacy and Safety of Remimazolam in Endoscopic Sedation—A Systematic Review and Meta-Analysis - Zhu, Xianlin; Wang, Hongbai; Yuan, Su; Li, Yinan; Jia, Yuan; Zhang, Zhe; Yan, Fuxia; Wang, Zaiping (Frontiers in Medicine, 2021)
Background: The aim of this systematic review and meta-analysis was to investigate the efficacy and safety of remimazolam in clinical endoscopic procedures sedation. Methods: The authors searched the databases of PubMed, Embase, and Cochrane Library for studies published until Jan 02, 2021, that reported remimazolam sedation for endoscopic procedures. The sedative efficiency and the incidence of adverse events were assessed as outcomes. Cochrane Review Manager Software 5.3 was used to perform the statistical analyses. Results: Seven relevant studies involving a total of 1,996 patients were identified. We conducted a meta-analysis of the different controls used in the studies, that is the placebo, midazolam, and propofol. The results demonstrated that remimazolam had a strong sedative effect, and its sedative efficiency was significantly higher than that of placebo (OR= 0.01, 95% CI: [0.00, 0.10], I2 =30%, p <0.00001). The sedative efficiency of remimazolam was significantly higher than that of midazolam (OR= 0.12, 95% CI: [0.08, 0.21], I2 =0%, p <0.00001) but lesser than that of propofol (OR= 12.22, 95% CI: [1.58, 94.47], I2 =0%, p =0.02). Regarding the adverse events, remimazolam is associated with a lower incidence of hypotension than placebo and midazolam. Similarly, remimazolam was associated with a lower incidence of hypotension and hypoxemia than propofol. Conclusions: Remimazolam is a safe and effective sedative for patients undergoing endoscopic procedures. The sedative efficiency of remimazolam was significantly higher than that of midazolam but slightly lower than that of propofol. However, respiration and circulation inhibitory effects of remimazolam were weaker than those of midazolam and propofol.